Islamic Guidance and Counseling for Adolescent Emotion Management - Ega Oktafiya; Muhamad Rozikan (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2026)
Adolescents' capacity to manage emotion is closely related to psychosocial adjustment, learning engagement, peer and teacher relationships, and mental health. In Islamic schools, counseling services may combine evidence-informed emotion-regulation support with religious resources that are meaningful to students. This study examined how Islamic Guidance and Counseling (IGC) was implemented to support students' emotion management at SMP Islam Ngadirejo, Temanggung, Indonesia, and identified the barriers encountered in practice. A qualitative descriptive field design was employed. Primary data were derived from interviews with the school counselor and students, while observations, documentation of counseling activities, and school-profile materials provided contextual evidence. Data were organized through reduction, display, and conclusion drawing, with source and technique triangulation used to strengthen interpretive credibility. Findings indicate a tiered service architecture comprising classroom guidance, group guidance, individual counseling, group counseling, home visits, and case conferences. These modalities were integrated with Qur'anic and Prophetic values and practices such as istighfar, Qur'an recitation, self-reflection, and encouragement of voluntary night prayer. The counselor adopted a proactive, firm-yet-persuasive, and collaborative approach involving teachers and families. Participants perceived improvements in students' emotional control and learning functioning, although the qualitative design does not permit causal claims. Major barriers included the image of counseling as disciplinary policing, reluctance to disclose personal concerns, limited time and personnel, inconsistent coordination, variable family involvement, and weak data management. The study suggests that Islamic school counseling is most promising when religious meaning-making is integrated with relational safety, confidentiality, explicit emotion-regulation skills, and school-wide coordination.